2012
DOI: 10.1007/s10021-012-9539-x
|View full text |Cite
|
Sign up to set email alerts
|

Century-Scale Responses of Ecosystem Carbon Storage and Flux to Multiple Environmental Changes in the Southern United States

Abstract: Terrestrial ecosystems in the southern United States (SUS) have experienced a complex set of changes in climate, atmospheric CO 2 concentration, tropospheric ozone (O 3 ), nitrogen (N) deposition, and land-use and land-cover change (LULCC) during the past century. Although each of these factors has received attention for its alterations on ecosystem carbon (C) dynamics, their combined effects and relative contributions are still not well understood. By using the Dynamic Land Ecosystem Model (DLEM) in combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
106
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 143 publications
(107 citation statements)
references
References 68 publications
1
106
0
Order By: Relevance
“…The DLEM is a highly integrated process-based ecosystem model, which combines biophysical characteristics, plant physiological processes, biogeochemical cycles, vegetation dynamics, and land use to make daily, spatially explicit estimates of carbon, nitrogen, and water fluxes and pool sizes in terrestrial ecosystems from site and regional to global scales (Lu and Tian, 2013;Tian et al, 2012. The DLEM is characterized of cohort structure, multiple soil layer processes, coupled carbon, water, and nitrogen cycles, multiple GHG emissions simulation, enhanced land surface processes, and dynamic linkages between terrestrial and riverine ecosystems (Liu et al, 2013;Tian et al, 2010.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The DLEM is a highly integrated process-based ecosystem model, which combines biophysical characteristics, plant physiological processes, biogeochemical cycles, vegetation dynamics, and land use to make daily, spatially explicit estimates of carbon, nitrogen, and water fluxes and pool sizes in terrestrial ecosystems from site and regional to global scales (Lu and Tian, 2013;Tian et al, 2012. The DLEM is characterized of cohort structure, multiple soil layer processes, coupled carbon, water, and nitrogen cycles, multiple GHG emissions simulation, enhanced land surface processes, and dynamic linkages between terrestrial and riverine ecosystems (Liu et al, 2013;Tian et al, 2010.…”
Section: Model Descriptionmentioning
confidence: 99%
“…From a socioeconomic perspective, present plantation forests in the CONUS generate positive economic profits along with providing good environmental services. From a carbon credit perspective, the plantation forests in the South are regarded as a major contributor to carbon sink in the CONUS and North America King et al, 2012;Tian et al, 2012Tian et al, , 2014; however, recent studies (Achat et al, 2015a, b;Nave et al, 2010) suggested that the shorter rotation age and some intensive management practices (e.g., site preparation for soil bedding, slash burning, and harvest residue raking) might reduce soil carbon stocks in plantation forests, implying that plantation forests could be a carbon source. From the hydrological perspective, plantation forests may increase water use and alter the water cycle due to higher productivity and management practices (e.g., short rotation, mechanic site preparation, and drainage), especially in the regions with strong precipitation limitation (Vose et al, 2012).…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…The model representation of underlying processes determining carbon assimilation and loss are described by Tian et al (2010a). Recently, we updated the model to the DLEM 2.0 to include the dynamic linkages between terrestrial and riverine ecosystems Tian et al, 2012). Here, we provide a brief description on how the DLEM simulates primary productivity (GPP and NPP) in the next section.…”
Section: Model Descriptionmentioning
confidence: 99%